Exploring Elderly Individuals' Social Representations in the Face of the COVID-19 Pandemic: A Psychosocial Approach (Research, Society and Development, 2023)
The present study aimed to grasp the Social Representations elaborated by the group of elderly individuals regarding the COVID-19 pandemic, using the Social Representations Theory as a theoretical framework. This was a field study, exploratory in nature, employing non-probabilistic sampling (Snowball method). A total of 43 (forty-three) elderly individuals participated in the study, comprising 14 women and 29 men. The instruments utilized included a sociodemographic questionnaire and a semi-structured interview. Data from the sociodemographic questionnaire were analyzed using descriptive statistics (SPSS). The narratives obtained through the semi-structured interview were processed using the ALCESTE software. In a broader context, this investigation may contribute to the development of effective evidence-based policies, considering the global challenges faced during the COVID-19 pandemic. The social representations shared and developed by the elderly in constructing meaning about COVID-19, their perception of the experience, and their views on vaccination, have shed light on aspects that could lead to prevention. In this regard, this study not only enriches our understanding of the perceptions of the elderly regarding the pandemic but also provides a solid foundation for informed decision-making, potentially influencing the planning of public health strategies and actions targeting this vulnerable population. The analysis of the Social Representations shared by the elderly may contribute to the promotion of preventive and enlightening approaches to address the challenges that emerged during the global COVID-19 crisis.